Functional analysis and treatment of aggression exhibited by cats toward humans during petting. Issue 1 (27th August 2021) - Fritz, Jennifer N.; Fletcher, Victoria L.; Dyer, Samantha P.; Carpenter, Kristin A.; Skrbec, Megan L.; Yankelevitz, Rachelle L.
Abstract : Human‐directed aggression is a common problem that can often result in rehoming or relinquishing the cat as well as injuries and infections for the human. Functional analyses (FAs) have been used to determine the cause of problem behavior by human and nonhuman animals, and treatments developed based on FA results have been proven effective. This study applied this methodology to assess and treat human‐directed aggression exhibited by 3 cats during petting. Results suggested that aggression during petting for all 3 cats was maintained by social‐negative reinforcement (escape from petting), and differential reinforcement of other behavior plus within‐session stimulus fading (escape contingent on the absence of aggression following a specified number of pets that systematically increased as aggression remained low) was effective in decreasing aggression for all 3 cats. All 3 cats were available for adoption through a rescue organization during the study, and all of the cats were adopted after completing treatment.